Educational Policies during the Colonial and Old Order Periods and Their Implications for Islamic Education in Indonesia - Hazis Daulay, Abdul; Helmiati; Hasyim, Hariza (Universitas Islam Negeri Raden Intan Lampung, 2026)
Educational policies in each historical period have had different orientations, thereby influencing the development of Islamic education in Indonesia. This study aims to analyze educational policies during the Dutch colonial period and the Old Order era, as well as their implications for Islamic education. The study employs a qualitative approach using library research. Data were obtained through a documentary study of relevant books, scholarly articles, and policy documents, which were then analyzed using a historical approach and content analysis. The results show that educational policies during the Dutch colonial period were discriminatory and oriented toward colonial administrative and economic interests, causing Islamic education to develop independently through pesantren and madrasahs outside the formal education system. Conversely, during the Old Order era, the government began to build a more inclusive national education system by accommodating religious education within the school curriculum. This shift in policy orientation spurred the transformation of Islamic education’s position from that of a marginalized institution to a recognized component of the national education system. These findings indicate that the dynamics of educational policy play a crucial role in shaping the development of Islamic education and its contribution to the nation’s character and identity.